Antioxidant Activity of Dewandaru Leaf (Eugenia Uniflora L.) Ethanol Extract and Determination of Total Flavonoid and Phenolic Content - Khoirul Anwar; Faridha Maera Lokana; Aqnes Budiarti (Sam Ratulangi University, 2022)
Dewandaru (Eugenia uniflora L.) is a plant that has antioxidant activities. The compounds contained phenolic compounds and flavonoids. This study aimed to test the antioxidant activity of the ethanol extract of Dewandaru leaves (Eugenia uniflora L.) with ABTS method and determine the content of flavonoid and total phenolic compounds. Ethanol extract of Dewandaru leaves was obtained by maceration using 96% ethanol. The ethanol extract of Dewandaru leaves identified the active compounds by FTIR (Fourier Transform Infra Red) and phytochemical screening. Ethanol extract of Dewandaru leaves was tested for its antioxidant activity using the ABTS method to obtaine the IC50 value and determined total flavonoid and phenolic content using UV/Vis spectrophotometry to obtain the levels (mg/g sample). The identification results show that the ethanol extract of Dewandaru leaves is a flavonoid compound of the dihydroflavonol type which has a bound OH functional group, aliphatic CH, C = O, C = C aromatic, C - O and aliphatic CH, and there are hydroxy groups on the C-3, C atoms. -5, and C-7. The results of phytochemical screening showed that the ethanol extract of Dewandaru leaves contains saponins, tannins, phenolics, and flavonoids. The ethanol extract of Dewandaru leaves has antioxidant activity with an IC50 value of 33.92 ppm and trolox with an IC50 value of 19.24 ppm. Based on the IC50 value, both are categorized very strong antioxidant activity. The total phenolic and total flavonoid levels were 327.52 mgGAE/g and 35.65 mgQE/g. Keywords: Antioxidant; Eugenia uniflora L.; flavonoid; phenolic Aktivitas Antioksidan Ekstrak Etanol Daun Dewandaru (Eugenia Uniflora L.) serta Penetapan Flavonoid dan Fenolik Total ABSTRAK Dewandaru (Eugenia uniflora L.) termasuk salah satu tanaman yang mempunyai khasiat antioksidan. Senyawa yang terkandung didalamnya antara lain senyawa fenolik dan flavonoid. Penelitian ini bertujuan untuk melakukan uji aktivitas antioksidan ekstrak etanol daun dewandaru (Eugenia uniflora L.) menggunakan metode ABTS dan menetapkan kandungan senyawa flavonoid dan fenolik total. Ekstrak etanol daun dewandaru diperoleh dengan cara maserasi menggunakan etanol 96 %. Ekstrak etanol daun dewandaru diidentifikasi senyawa aktif dengan FTIR (Fourier Transform Infra Red) dan skrinning fitokimia. Ekstrak etanol daun dewandaru diuji aktivitas antioksidan menggunakan metode ABTS sehingga diperoleh nilai IC50. Selanjutnya ekstrak etanol daun dewandaru ditetapkan kandungan flavonoid dan fenolik totalnya secara spektrofometri UV/Vis hingga diperoleh kadarnya (mg/g sampel). Hasil identifikasi menunjukkan ekstrak etanol daun dewandaru mengandung senyawa golongan flavonoid jenis dihidroflavonol yang mempunyai gugus fungsi OH terikat, CH alifatik, C = O, C = C aromatik, C – O dan CH alifatik, serta terdapat gugus hidroksi pada atom C-3, C-5, dan C-7. Hasil skrining fitokimia menunjukkan bahwa ekstrak etanol daun dewandaru mengandung senyawa saponin, tanin, fenolik, dan flavonoid. Ekstrak etanol daun dewandaru memiliki aktivitas antioksidan dengan nilai IC50 sebesar 33,92 ppm dan trolox dengan nilai IC50 sebesar 19,24 ppm. Berdasarkan nilai IC50 keduanya dikategorikan memiliki aktivitas antioksidan yang sangat kuat. Sedangkan kadar fenolik total serta flavonoid total sebesar 327,52 mgGAE/g dan 35,65 mgQE/g. Kata kunci: antioksidan; Eugenia uniflora L.; fenolik; flavonoid